Peningkatan Kualitas Usaha Mikro Kecil Menengah (UMKM) Melalui E-Commerce di Kampung Patin Kecamatan XIII Koto Kampar - Rohayati Rohayati; Rafdeadi Rafdeadi; Nur Alhidayatillah (Lembaga penelitian dan pengabdian kepada masyrakat, 2021)
Advances in communication and information technology make humans very dependent on the media, be it mainstream media or social media. One of the significant effects of information technology is the change in the buying and selling system from conventional methods to more modern ones, namely through the internet or what we call e-commerce. However, not all small and medium-sized businesses have used e-commerce to maximize sales, this is as experienced by catfish farmers in Koto Masjid Village, Kec. XIII Koto Kampar. This service aims to train small and medium business actors to use e-commerce media in marketing their products to increase income and expand consumer targets. The service technique is carried out directly and is applicable, through the presentation method (lecture) and training on e-commerce techniques directly (applicative), for further assistance. The training participants are people who have a catfish farming business in Koto Masjid Village. The result of this service is that the community can apply e-commerce so that it can be a solution to develop the business they have built, innovate and of course improve the welfare of the farmers.